AXIOLOGY AND LINGUISTICS: ONE REFLECTION ABOUT THE SOCIAL VALUES AND THE LIE IN THE POLITICIAN’S CURRICULUM (PERcursos Linguísticos, 2021)
This article proposes a reflection about values in education for a democratic society, considering political news (EXAME, 2019), justified by the fact that the school is committed to a relationship of political action forces that often disqualifies it. The methodology makes the interface Axiology (ARANHA, 1989; FREIRE, 1996), Textual Linguistics (KOCH, 2011; CAVALCANTE, 2016) and pragmatics (GRICE, 1982). From a linguistic perspective, the analysis perceived a strategic textual organization of the news, on the part of the journalist, for disapproval of the lie and exposure of liars, and, on the part of the politicians, the denial of the lie and the effort to mitigate or recategorize it. From a sociopolitical perspective, the process of raising awareness about values must make the connection between school and life. Thus, at the same time that ethics need to be part of the student's political education to (co) manage the city for the common good, it is expected that government officials have this training and be examples of citizenship for students, which the reported fact contradicts. Finally, from an educational perspective, institutions and educators committed to the critical and democratic ideal need to play their ethical role through the necessary exercise of dialogic interaction and respectful human coexistence, to form a critical citizen and a democratic society.